Sharing the Caring? The Gender Division of Care Work during the COVID-19 Pandemic in Germany - Jonas Jessen; C. Katharina Spiess; Sevrin Waights; Katharina Wrohlich (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic and related closures of daycare centers and schools significantly increased the amount of care work done by parents. There is much speculation over whether the pandemic increased or decreased gender equality in parental care work. Based on representative data for Germany we present an empirical analysis that shows greater support for the latter rather than the former hypothesis. A key finding is that there is a significant increase in the number of couples where the mother is left completely or almost completely alone with the care work. We see only small increases in the prevalence of fathers doing more than mothers or in splitting these tasks 50:50. Additionally we find that the increase in mothers solely responsible for care work is greatest when the mother alone works from home. The division of care work is perceived very differently by mothers and fathers, a difference that also increased during the pandemic.
Keywords: D13; J16; J22; 330; gender division; domestic work; child care; day care; COVID-19